Unveiling Anthraquinones: Diverse Health Benefits of an Essential Secondary Metabolite - Khatoon, Mushfa; Dubey, Amita; Janhvi, Km (Recent Patents on Biotechnology, 2025)
Since ancient times, plants have been used as a remedy for numerous diseases. The pharmacological properties of plants are due to the presence of secondary metabolites like terpenoids, flavonoids, alkaloids, etc. Anthraquinones represent a group of naturally occurring quinones found generously across various plant species. Anthraquinones attract a significant amount of attention due to their reported efficacy in treating a wide range of diseases. Their complex chemical structures, combined with inherent medicinal properties, underscore their potential as agents for therapy. They demonstrate several therapeutic properties such as laxative, antitumor, antimalarial, antibacterial, antifungal, antioxidant, etc. Anthraquinones are found in different forms (derivatives) in plants, and they exhibit various medicinal properties due to their structure and chemical nature. The precursors for the biosynthesis of anthraquinones in higher plants are provided by different pathways such as plastidic hemiterpenoid 2-C-methyl-D-erthriol4-phosphate (MEP), mevalonate (MVA), isochorismate synthase and polyketide. Anthraquinones possess several medicinal properties and a complex biosynthetic pathway, making them good candidates for patenting new products, synthesis methods, and biotechnological production advancements. By conducting a thorough analysis of scientific literature, this review provides insights into the intricate interplay between anthraquinone biosynthesis and its broad-ranging contributions to human health.
Keywords: alkaloids